THE RELATIONSHIP OF FAMILY SUPPORT WITH ANXIETY LEVEL AMONG WORKERS WITH COVID-19 - AYAMAH AYAMAH; MAELIA UNAYAH; INDRI FADIYA (NURSING ANALYSIS: Journal of Nursing Research, 2022)
ABSTRACTCovid-19 is an infectious disease caused by a new variant of the coronavirus in December 2019. This covid-19 pandemic has caused an increasing level of anxiety and psychology for Covid-19 patients in society.  Psychological responses that occur due to anxiety require mental support from the family to increase the patient's enthusiasm for life. The purpose of this study was to determine the relationship between family support and anxiety levels in workers with Covid-19 at Kimia Farma Apotek Unit Business Bogor. This research method is a quantitative study with a cross sectional design, data was collected by online questionnaire using Google Form, the number of samples was 60 Covid-19 patients at Kimia Farma Apotek Unit Business Bogor. The results of this study can be obtained that the results of high family support values are 36 respondents (60.00%), and moderate anxiety are 29 respondents (48.33%).  The results of the chi-square test obtained a p value of 0.004 < = 0.05. So it can be concluded that there is a relationship between family support and anxiety levels in workers with Covid-19 at Kimia Farma Apotek Unit Business Bogor. Suggestions from the results of this study are expected that the family can provide support and motivation to patients who are confirmed to be covid-19 so that patients are able to control their anxiety. Keywords: Family Support, Anxiety Level, Workers with Covid-19 HUBUNGAN DUKUNGAN KELUARGA DENGANTINGKAT KECEMASAN PADA PEKERJA DENGAN COVID-19 ABSTRAKCovid-19 adalah penyakit menular yang disebabkan oleh coronavirus varian baru pada Desember 2019. Pandemi covid-19 ini telah menyebabkan tingkat kecemasan dan psikologis pasien covid-19 di masyarakat yang semakin meningkat. Respon psikologis yang terjadi akibat kecemasan memerlukan dukungan mental dari keluarga untuk meningkatkan semangat hidup pasien. Tujuan Penelitian ini adalah untuk mengetahui Hubungan Dukungan Keluarga Dengan Tingkat Kecemasan Pada Pekerja Dengan Covid-19 Di Kimia Farma Apotek Unit Bisnis Bogor. Metode penelitian ini merupakan penelitian kuantitatif dengan desain cross sectional, data dikumpulkan dengan kuesioner secara online menenggunakan Google Form, jumlah sampel sebanyak 60 pekerja dengan covid-19 di Kimia Farma Apotek Unit Bisnis Bogor. Hasil Penelitian ini dapat diperoleh bahwa hasil nilai dukungan keluarga tinggi sebanyak 36 responden (60,00%), dan kecemasan sedang sebanyak 29 responden (48,33%). Hasil uji chi-square diperoleh nilai p value sebesar 0,004 < ɑ = 0,05. Maka dapat disimpulkan bahwa ada hubungan dukungan keluarga dengan tingkat kecemasan pada pekerja dengan covid-19 di Kimia Farma Apotek Unit Bisnis Bogor. Saran dari hasil penelitian ini diharapkan keluarga dapat memberi dukungan serta motivasi terhadap pasien yang terkonfirmasi covid-19 sehingga pasien mampu mengendalikan kecemasannya. Kata Kunci : Dukungan Keluarga, Tingkat Kecemasan, Pekerja Dengan Covid-19